Social Media Rumors in Time of Corona Pandemic, Why & How is Criminalized? (Comparative Study) - ALSHIBLE, Mohamad (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).03, 2020)
No one in the world does not know what Corona is as a global pandemic, which the Secretary-General of the WHO has declared as ‘the enemy of humanity’. Yes, it is the enemy of humanity; the whole humans rose up to prevent it through several aspects. We are – as lawmen – responsible for the legal sides. All of us have become so miserable that many sciences are terrified of rumors and false news. The real news leaves pain in the souls, so what about that are false, whether it was broadcast or transmitted with intent or unintentionally The main objective of this article is to examine the Jordanian legislator attitude in regard of social media rumors during Corona pandemic (COVID19), in comparative to the Chinese legislator. The study shows that the opportunity to punish rumors at the time of the pandemic may be unavailable or weak and not coherent in Jordanian laws in comparison with other legislations, especially in Chinese laws. The study will also show if rumors were included in relative International treaties. The In respect to the methodology of this article, the author followed the descriptive and analytical approaches of the related Jordanian Penal laws in comparative with the Chinese Regulations in cybercrimes, by explaining the extent to which rumor crimes is punished in Jordan according to legal methods of analysis in comparative to the Chinese legal attitude.